Long Term Influence of Fertility and Rotation on Soil Nitrification Potential and Nitrifier Communities - Raglin, Sierra S.; Soman, Chinmay; Ma, Yanjun; Kent, Angela D. (Frontiers in Soil Science, 2022)
The agricultural imprints on soil microbial processes manifest at various timescales, leaving many temporal patterns to present slowly. Unfortunately, the lack of long-term continuous agricultural field sites in North America has left gaps in our understanding of agricultural management on biogeochemical processes and their controlling microbiota. Nitrification, ammonium oxidation by bacteria and archaea, is a critical control point in terrestrial nitrogen fluxes by oxidizing cationic ammonium to anionic nitrate, promoting nitrate leaching. Moreover, nitrous oxide is produced during nitrification, contributing to massive nitrous oxide emissions from fertilized agroecosystems. Nitrification is sensitive to many macro and micro-ecological filters, as nitrifiers are obligate aerobes and are sensitive to numerous non-growth substrates and metal ions. This study sought to understand the long-term implications of various rotation and fertilizer regimes on nitrification potential and nitrifying bacterial communities in the Morrow Plots (Urbana, IL). The Morrow Plots was established in 1876 and are the longest continuous field experiments in North America, making it the only site in America capable of assessing the impact of over 140 years of agricultural management on nitrification. The Morrow Plots contrasts fertilizer (manure, inorganic, unfertilized) and rotation (continuous corn, corn-soy, corn-oat alfalfa), allowing us to explore how conventional versus regenerative agriculture practices impact nitrifier communities. The results of this study suggest that fertilizer and rotation interact to promote distinct bacterial nitrifier communities. Nitrification potential is highest in manure corn-oat-alfalfa plots, suggesting ammonium availability is not solely responsible for active nitrifier communities. Various soil chemical variables, like CEC, Mg, and Ca, significantly influenced nitrifier community beta-diversity, using 16S rRNA amplicon sequencing, suggesting long-term accumulation of specific cations diverge microbial community assembly. While this study only uses nitrification potential enzyme activity instead of isotope analyses, it sheds light on the importance of various physiochemical drivers on nitrification potential and communities. The results support the need for a more precise exploration of the mechanisms controlling field-scale nitrification rates over large temporal scales. Put together, this study supports the importance of long-term field sites for understanding agricultural manipulations of microbial biogeochemical cycling and sheds light on the micronutrients influencing nitrifier communities and potential activity.